1990
DOI: 10.1002/jat.2550100204
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal‐dependent leucopenia after short‐term exposure to various airborne irritants in rats

Abstract: Leucopenia without any change in differential or red blood cell counts was observed in rats exposed for 4 h to increasing concentrations of the following airborne irritants: acetic acid, benzyl chloride, 1,2-dichlorobenzene, ethyl acetate, ethyl acrylate, formaldehyde, isophorone, mesityl oxide, phenol, styrene, toluene diisocyanate and vinyl toluene. This effect was abolished by adrenalectomy. Vinyl toluene and 1,2-dichlorobenzene induced leucopenia at levels as low as their current occupational standards of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Brondeau et al (1990) found that exposure to airborne irritants (including formaldehyde) caused leukopenia at irritant levels (≥43 ppm for formaldehyde, in an exposure-dependent manner) over a 4-hour exposure, and that this effect was prevented by removal of the adrenal gland, suggesting a possible role for this gland in apparent hematological effects. Sari et al (2004) also found that relatively low concentrations (0.08, 0.4, and 2.0 ppm) of formaldehyde increased hypothalamus/pituitary/adrenal (HPA) axis activity by increasing the numbers of both hypothala-mus corticotropin releasing hormone-immunoreactive neurons and pituitary adrenocorticotropin hormone (ACTH)-immunoreactive cells in mice.…”
Section: Weight Of Evidence Regarding Hematotoxicity From Formaldementioning
confidence: 98%
“…Brondeau et al (1990) found that exposure to airborne irritants (including formaldehyde) caused leukopenia at irritant levels (≥43 ppm for formaldehyde, in an exposure-dependent manner) over a 4-hour exposure, and that this effect was prevented by removal of the adrenal gland, suggesting a possible role for this gland in apparent hematological effects. Sari et al (2004) also found that relatively low concentrations (0.08, 0.4, and 2.0 ppm) of formaldehyde increased hypothalamus/pituitary/adrenal (HPA) axis activity by increasing the numbers of both hypothala-mus corticotropin releasing hormone-immunoreactive neurons and pituitary adrenocorticotropin hormone (ACTH)-immunoreactive cells in mice.…”
Section: Weight Of Evidence Regarding Hematotoxicity From Formaldementioning
confidence: 98%
“…The reaction was stress-induced and mediated via the hyyophysis-adrenal axis. Thus, an acetic acid exposure of rats for 4 hrs at 135 pprn (330 mg/m3) had no effect on the WBC count, whereas high concentrations (450-598 ppm) gave rise to a concentration-dependent decrease (Brondeau et al, 1990).…”
Section: Acute Effects In Animalsmentioning
confidence: 88%
“…This finding was unexpected since benzyl chloride was not mentioned in any printery studied uncovered by our extensive literature review. It is classified by IARC as probably carcinogenic, and in rats exposure has been shown to cause leucopenia (Brondeau et al 1990).…”
Section: Discussionmentioning
confidence: 99%